Of bison bones and fine China : a vegan approach to genocide on the Plains - Madsen, Deborah Lea (2023)
The digital prose-poem, “Bone China” (2015), by Canadian First Nations writer Paul Seesequasis responds to three historical photographs from the Saskatoon Public Library Archives (dated 1878, 1890, 1891) that depict towering stacks of bison bones, waiting to be shipped for industrial processing into products that included fine bone chinaware. Reading Seesequasis' poetic chinaware intersectionally, from an ethical vegan perspective, exposes the multiple metonymic significances of the late nineteenth-century bison Holocaust or “animal genocide” described by Anishinaabe theorist Gerald Vizenor. The mass slaughter of the bison not only brought Plains nations into submission to the US settler-colonial state but the physical elimination of Native presence (both human and other-than-human) worked to legitimize westward territorial expansion. Not even bones remained as the literal sign of prior occupation; settler pioneers, following the hunters and skinners, collected bison bones to sell for industrial purposes such as the production of bone china in the potteries of Staffordshire and elsewhere. This presentation contextualizes the intersectionality of Paul Seesequasis' poem via the human-animal discourses of films such as Dances with Wolves (1990) and Avatar (2009), and the video game Red Dead Redemption , to uncover the speciesist “human exceptionalism” that grounds the ideology of Manifest Destiny, the ongoing processes of settler colonization, and the commercial interests it continues to serve.